Health costs in anthroposophic therapy users: a two-year prospective cohort study - Willich Stefan N; Ziegler Renatus; Glockmann Anja; Witt Claudia M; Hamre Harald J; Kiene Helmut (BMC, 2006)
Abstract Background Anthroposophic therapies (counselling, special medication, art, eurythmy movement, and rhythmical massage) aim to stimulate long-term self-healing processes, which theoretically could lead to a reduction of healthcare use. In a prospective two-year cohort study, anthroposophic therapies were followed by a reduction of chronic disease symptoms and improvement of quality of life. The purpose of this analysis was to describe health costs in users of anthroposophic therapies. Methods 717 consecutive outpatients from 134 medical practices in Germany, starting anthroposophic therapies for chronic diseases, participated in a prospective cohort study. We analysed direct health costs (anthroposophic therapies, physician and dentist consultations, psychotherapy, medication, physiotherapy, ergotherapy, hospital treatment, rehabilitation) and indirect costs (sick leave compensation) in the pre-study year and the first two study years. Costs were calculated from resource utilisation, documented by patient self-reporting. Data were collected from January 1999 to April 2003. Results Total health costs in the first study year (bootstrap mean 3,297 Euro; 95% confidence interval 95%-CI 3,157 Euro to 3,923 Euro) did not differ significantly from the pre-study year (3,186 Euro; 95%-CI 3,037 Euro to 3,711 Euro), whereas in the second year, costs (2,771 Euro; 95%-CI 2,647 Euro to 3,256 Euro) were significantly reduced by 416 Euro (95%-CI 264 Euro to 960 Euro) compared to the pre-study year. In each period hospitalisation and sick-leave together amounted to more than half of the total health costs. Anthroposophic therapies and medication amounted to 3%, 15%, and 8% of total health costs in the pre-study year, first year, and second study year, respectively. The cost reduction in the second year was largely accounted for by a decrease of inpatient hospitalisation, leading to a hospital cost reduction of 519 Euro (95%-CI 377 Euro to 904 Euro) compared to the pre-study year. Conclusion In patients starting anthroposophic therapies for chronic disease, total health costs did not increase in the first year, and were reduced in the second year. This reduction was largely explained by a decrease of inpatient hospitalisation. Within the limits of a pre-post design, study findings suggest that anthroposophic therapies are not associated with a relevant increase in total health costs.